Peru : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper focuses on policies to promote high, sustainable growth in Peru, the risks posed by dollarization, and key medium-term fiscal issues of decentralization and social security reform. The paper identifies the main impediments to output and employment growth and proposes steps to remove them. It uses a balance sheet approach to analyze Peru's highly dollarized economy, and finds that the factors explaining Peru's relatively low international trade levels are related to the impediments to growth. The paper also looks at the main impediments to high, sustainable output, and employment growth in Peru.